Complete sequence of the chloroplast genome of Asarum heterotropoides (Aristolochiales: Asarum L.) - Rong Zhao; Yan-Ping Xing; Hai-Bo Yin; Ting-Guo Kang (Mitochondrial DNA. Part B. Resources, 2019)
This article aims to introduce the Asarum heterotropoides complete chloroplast genome sequence information. Asarum heterotropoides complete length of 159,944 BP and the total content of GC was 38.5%, with SSC (16,677 BP) and LSC (88,253 BP) to a separate IR (27,261 BP) consisting of four typical structures. Asarum heterotropoides CP genome encodes 152 unique genes, including 103 protein-encoding genes, 41 tRNA genes, and eight rRNA genes, and 44 copies in the IR region. One gene contains two genes in the 15 genes which contain one intron. The phylogenetic trees are based on 15 plants. The determination of A. heterotropoides was closely related to the phylogenetic position of Ceratophyllum demersum and its relationship with Chloranthus japonicus.